2003
DOI: 10.1210/jc.2003-030097
|View full text |Cite
|
Sign up to set email alerts
|

The Use in Clinical Practice of Parathyroid Hormone Normative Values Established in Vitamin D-Sufficient Subjects

Abstract: We have found recently that excluding subjects with low serum 25OHD has a significant impact on the PTH reference range (10 -46 ng/liter instead of 10 -65 ng/liter with the same assay). However, before being used routinely, this new range had to be clinically validated. We thus reviewed the chart of 708 consecutive osteopenic patients who were referred to our unit for a biological exploration in search of secondary causes for their low bone mass. They were classified into two groups. Group 1 (n ‫؍‬ 360) includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 34 publications
4
43
2
10
Order By: Relevance
“…After exclusion (Fig. 1), the study consisted of 177 hypercalcaemic patients with a mean of two to four calcium measurements and plasma intact PTH in the upper one-third of the normal range or elevated (P-PTH O5 pmol/l) (31). The patients were then divided into two groups, with or without renal calcification on spiral CT scan, and the blood and urine samples were compared.…”
Section: Methodsmentioning
confidence: 99%
“…After exclusion (Fig. 1), the study consisted of 177 hypercalcaemic patients with a mean of two to four calcium measurements and plasma intact PTH in the upper one-third of the normal range or elevated (P-PTH O5 pmol/l) (31). The patients were then divided into two groups, with or without renal calcification on spiral CT scan, and the blood and urine samples were compared.…”
Section: Methodsmentioning
confidence: 99%
“…(27,28). After parathyroid surgery, histopathological examination revealed adenoma(s) in 119 of the patients, hyperplasia in 26, and combined adenoma and hyperplasia in 2 patients.…”
Section: Patients and Materialsmentioning
confidence: 99%
“…They found that when 25-OHD levels were considered, the upper limits of "normal" of PTH declined from 65 pg/mL to 46 pg/mL in subjects with 25-OHD levels above 30 nmol/L, a change that would have clinical ramifications. Subsequently, these investigators validated their proposal of 46 pg/ mL as the upper limit of the reference range of PTH by a review of medical records in patients with osteopenia (26). In an editorial accompanying their publication, however, their conclusions were questioned (27).…”
Section: Introductionmentioning
confidence: 99%